Digital Islam and Muslim Millennials: How Social Media Influencers Reimagine Religious Authority and Islamic Practices - Zaid, Bouziane; Fedtke, Jana; Shin, Don Donghee; El Kadoussi, Abdelmalek; Ibahrine, Mohammed (Religions (Basel, Switzerland ), 2022)
Digital platforms have empowered individuals and communities to re-negotiate long-established notions of religion and authority. A new generation of social media influencers has recently emerged in the Muslim world. They are western-educated, unique storytellers, and savvy in digital media production. This raises new questions on the future of Islam in the context of emerging challenges, such as the openness of technology and the often-perceived closedness of religious and cultural systems within Muslim societies. This paper uses a multiple case research design to examine the roles of social media influencers in reimagining Islam and reshaping spiritual beliefs and religious practices among young people in the Gulf Region, the Arab world, and beyond. We used thematic analysis of the Instagram and YouTube content of four social media influencers in the Gulf Region: Salama Mohamed and Khalid Al Ameri from the United Arab Emirates, Ahmad Al-Shugairi from Saudi Arabia, and Omar Farooq from Bahrain. The study found that social media influencers are challenging traditional religious authorities as they reimagine Muslim identities based on a new global lifestyle.